Surfing - Rice, E. L. (The Journal of Sports Medicine and Physical Fitness, 2021)
Surfing is one of the oldest sports known to exist, originating over 800 years ago and spreading from Polynesia to eventually encompass most every corner of the globe. Beginning in popularity with Hawaiian Kings and aristocracy, it has now spread to over 35 million people world-wide, and now is one of the newly admitted sports for the 2020 Summer Tokyo Olympic Games. Surfing abilities and techniques have evolved in parallel with the development of lighter and more versatile surfboards. There are limited studies documenting in depth the frequency and type of acute and overuse surfing injuries, but the sport is deemed to be significantly safer than collision sports like rugby or American football, with most injuries being of mild to moderate severity. Fatal injuries are relatively rare. There are some hazardous environmental injuries, but most are mild in severity and largely preventable. The governance of surfing is under the auspices of the International Surfing Association, which regulates surfing of all types. Multiple non-governmental organizations have arisen which serve to promote the popularity, quality, advancement, research, education and safety of surfing.